Influenza Viral Vectors Expressing Two Kinds of HA Proteins as Bivalent Vaccine Against Highly Pathogenic Avian Influenza Viruses of Clade 2.3.4.4 H5 and H7N9 - Li, Jinping; Hou, Guangyu; Wang, Yan; Wang, Suchun; Peng, Cheng; Yu, Xiaohui; Jiang, Wenming (Frontiers in Microbiology, 2018)
The H5 and H7N9 subtypes of highly pathogenic avian influenza viruses (HPAIVs) in China pose a serious challenge to public health and the poultry industry. In this study, a replication competent recombinant influenza A virus of the Í5N1 subtype expressing the H7 HA1 protein from a tri-cistronic NS segment was constructed. A heterologous dimerization domain was used to combine with the truncated NS1 protein of 73 amino acids to increase protein stability. H7 HA1, nuclear export protein coding region, and the truncated NS1 were fused in-frame into a single open reading frame via 2A self-cleaving peptides. The resulting PR8-H5-NS1(73)H7 stably expressed the H5 HA and H7 HA1 proteins, and exhibited similar growth kinetics as the parental PR8-H5 virus in vitro. PR8-H5-NS1(73)H7 induced specific hemagglutination inhibition (HI) antibody against H5, which was comparable to that of the combination vaccine of PR8-H5 and PR8-H7. The HI antibody titers against H7 virus were significantly lower than that by the combination vaccine. PR8-H5-NS1(73)H7 completely protected chickens from challenge with both H5 and H7 HPAIVs. These results suggest that PR8-H5-NS1(73)H7 is highly immunogenic and efficacious against both H5 and H7N9 HPAIVs in chickens. Highlights: - PR8-H5-NS1(73)H7 simultaneously expressed two HA proteins of different avian influenza virus subtypes. - PR8-H5-NS1(73)H7 was highly immunogenic in chickens. - PR8-H5-NS1(73)H7 provided complete protection against challenge with both H5 and H7N9 HPAIVs.